1994
DOI: 10.1016/1044-0305(94)85058-5
|View full text |Cite
|
Sign up to set email alerts
|

The Mass Spectrometry of Helical Unfolding in Peptides

Abstract: Two model peptides, melittin and a growth hormone releasing factor (GRF) analog, have been studied by mass spectrometry and tandem mass spectrometry during the course of their deuterium exchange. Both peptides are known from previous work to form α-helices in solution. When the peptides are exposed to deuterated solvents, their masses increase as deuterium atoms replace protons in the exchangeable sites of the peptides. The mass spectrometry results clearly indicate multiple populations of exchangeable protons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
75
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(76 citation statements)
references
References 26 publications
1
75
0
Order By: Relevance
“…The actual gain in spatial resolution depends on the size of the peptides and is often in the range of 5-10 residues. Higher spatial resolution has been obtained by using multiple proteases (27), differences in overlapping fragments (29), and collision-induced dissociation (MS/MS) (10,35,36). The success of all of these approaches depends on being able to digest proteins under conditions where isotope exchange is slow.…”
Section: Discussionmentioning
confidence: 99%
“…The actual gain in spatial resolution depends on the size of the peptides and is often in the range of 5-10 residues. Higher spatial resolution has been obtained by using multiple proteases (27), differences in overlapping fragments (29), and collision-induced dissociation (MS/MS) (10,35,36). The success of all of these approaches depends on being able to digest proteins under conditions where isotope exchange is slow.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that proton mobility within smaller protonated gas-phase peptide ions can often be sufficiently rapid to scramble deuterium labeling (28). However, recent findings of Anderegg et al (17) and Deng et al (18) have shown that under certain conditions, hydrogen exchange at individual peptide amide linkages can be determined by collision-induced dissociation MS. The results obtained in the present study are fully consistent with the expected exchange properties of the peptides based on the model in Fig.…”
Section: Esi Ms͞msmentioning
confidence: 99%
“…For a first hand view, gas-phase fragmentation in the mass spectrometer may appear to be the logical choice for an auxiliary method providing the desired site-specific informa-tion. Accordingly it has been widely adopted in the attempt to identify specific sites that have become deuterated in solution 1 H/ 2 H exchange experiments (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). It is, however, mandatory for this approach that the level of intramolecular hydrogen ( 1 H/ 2 H) migration upon ion activation is negligible.…”
mentioning
confidence: 99%